The effects of boron addition on the magnetic and mechanical properties of NiMnSn shape memory alloys - Aydogdu, Y.; Turabi, A. S.; Aydogdu, A.; Kok, M.; Yakinci, Z. D.; Karaca, H. E. (Springer, 2016)
The effects of boron addition on the microstructure, magnetic, mechanical, and shape memory properties of Ni50Mn40-xSn10Bx (at.%) (x = 1, 2, 3, 4, 6, 8) polycrystalline alloys were systematically investigated. It was revealed that transformation temperatures, magnetic behavior, mechanical, and shape memory properties can be tailored by B content. Transformation temperatures were decreased while saturation magnetization was increased with the addition of boron. In addition to magnetic behavior, ferromagnetic austenite transforms to weakly magnetic martensite, and then, martensite becomes ferromagnetic during cooling. The low amount of B addition (up to 4 %) to NiMnSn creates the second phase which provides higher strength and ductility. However, the high volume fraction of the second phase reduces the shape recovery because the phase transformation does not occur in the second phase. Brittleness takes place when the B amount is more than 6 % in NiMnSnB alloys. The amount of boron content in the NiMnSnB alloys plays a significant role to modify the magnetic, mechanical, and shape memory properties.
Keywords: Shape memory effect; Boron addition; Saturation magnetization; Phase transformation; Thermal characterization; Composition alteration